Hypokalemic Paralysis: A Hidden Card of Several Autoimmune Diseases - Velarde-Mejía, Yelitza (Clin Med Insights Arthritis Musculoskelet Disord, 2017)
Acute hypokalemic paralysis is a rare and potentially fatal condition, with few related causes, one of which highlights distal renal tubular acidosis (dRTA). Distal renal tubular acidosis is a rare complication of several autoimmune diseases such as systemic lupus erythematosus, Sjögren’s syndrome, and Hashimoto thyroiditis. We report a case of a lupic patient who presented rapidly progressive quadriparesis in the context of active renal disease. Research revealed severe refractory hypokalemia, metabolic acidosis, and alkaline urine suggestive of dRTA. We diagnosed Sjögren’s syndrome based on sicca symptoms, an abnormal salivary glands’ nuclear scan and the presence of anti-Ro/SSA and anti-La/SSB. In addition, the finding of thyroid peroxidase, thyroglobulin antibodies, and hypothyroidism led us to the diagnosis of Hashimoto thyroiditis. Due to the active renal involvement on the context of systemic lupus erythematosus and Sjögren’s syndrome, the patient received immunosuppression with rituximab, resulting in a progressive and complete improvement.